In-House Training Modules on Learning Media to Improve Information and Communication Technology Competence in Elementary School Teachers - Panjaitan, Mei Sarmauli; Harapan, Edi; Eddy, Syaiful (research, training and philanthropy institution Natural Aceh, 2024)
In-house training (IHT) programs effectively address educational challenges in schools through a thorough needs analysis. While IHT programs are frequently conducted, the primary focus should be on enhancing the quality of training to meet the specific needs of institutions, roles, and individuals involved. At SDN 98, a notable issue is the low utilization of technology in the learning process despite adequate multimedia facilities. Among 17 classroom teachers, fewer than 25% are proficient in using computers for instruction, and only one or two teachers regularly use laptops. The use of LCD projectors is also rare. This situation highlights the urgent need to improve teachers' information and communication technology (ICT) skills. Consequently, this Study aims to enhance the ICT competencies of SDN 98 teachers through targeted training and the development of IHT modules. The research employs a research and development (R&D) method that includes eight stages: initial research, planning, product design, validation, revision, limited trials, and field trials. The developed IHT module received excellent evaluations, with an average score of 4.49 from respondents and 4.56 from instructors, indicating its practicality and effectiveness in enhancing teachers' ICT competencies.